Proceedings of the VII European Congress on Computational Methods in Applied Sciences and Engineering (ECCOMAS Congress 2016) 2016
DOI: 10.7712/100016.2164.10112
|View full text |Cite
|
Sign up to set email alerts
|

An Analytical Model for Dynamic Response of an Elastic Sdof System Fixed on Top of a Rocking Single-Story Frame Structure: Experimental Validation

Abstract: Abstract. It has been shown that assemblies of large rocking bodies

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
18
0
1

Year Published

2017
2017
2021
2021

Publication Types

Select...
5
1

Relationship

2
4

Authors

Journals

citations
Cited by 12 publications
(20 citation statements)
references
References 13 publications
1
18
0
1
Order By: Relevance
“…

A rocking podium structure is a class of structures consisting of a superstructure placed on top of a rigid slab supported by free-standing columns. This was experimentally confirmed for other elastic uplifting systems [32,34,57].

Uplift works as a mechanical fuse that limits the forces transmitted to the superstructure, while rocking enables large lateral displacements.…”
mentioning
confidence: 56%
“…

A rocking podium structure is a class of structures consisting of a superstructure placed on top of a rigid slab supported by free-standing columns. This was experimentally confirmed for other elastic uplifting systems [32,34,57].

Uplift works as a mechanical fuse that limits the forces transmitted to the superstructure, while rocking enables large lateral displacements.…”
mentioning
confidence: 56%
“…1), 2 linking plates (Nr. 26 Further investigation of contact surface stiffness and imperfection effects on rocking motion are available in ElGawady et al 44 and Wittich and Hutchinson. 3).…”
Section: Shaking Table Testsmentioning
confidence: 99%
“…16,17 As the response of the rocking oscillator is highly nonlinear because of its negative stiffness, 18 many have suggested treating the rocking oscillator as a "chaotic system," in the sense that small perturbations of its governing parameters (be it the oscillator properties or the excitation) result to widely diverging outcomes. 26 This has generated a discussion on Housner's approach to determine the energy losses during impact and has resulted in various different energy dissipation models. Even if the coefficient of restitution is estimated accurately, or determined experimentally, the rocking oscillator is so sensitive that predicting the entire seismic response time history is practically impossible.…”
Section: Introductionmentioning
confidence: 99%
“…It represents structures that are designed to rock and their contact surfaces are designed such that the impact forces are concentrated as close to the corner as possible, in an e↵ort both to increase damping and to decrease the uncertainty concerning the position of the impact forces. It has been shown [27] that, even if the impact forces are forced by design to act as close to the corner as possible, and even if this results to an excellent prediction of the coe cient of restitution, the rocking problem is so sensitive that it is impossible to predict the entire time history response. Thus, the need for probabilistic treatment arises.…”
Section: Rocking Specimenmentioning
confidence: 99%
“…Researchers that have tried to experimentally validate Housner's model [20][21][22][23][24][25][26] have shown that, given the modelling uncertainty (especially of the one related to impact), it is di cult to confidently predict the time history response of a rocking block to a specific ground motion. Even if the coe cient of restitution is relatively well predicted, or determined via experiments, the response of the system to a ground motion is so sensitive that predicting the whole time history is practically impossible [27]. This has generated a lot of discussion about Housner's approach to determine the energy losses during impact and has resulted in various di↵erent energy dissipation models [28][29][30][31][32][33][34][35][36][37].…”
Section: Introductionmentioning
confidence: 99%